Evaluation of the functional condition of patients qualified for knee alloplastics - Waldon, Karol; Szczypiór-Piasecka, Karina; Mińko, Alicja; Antczak, Krzysztof; Orłowska, Aleksandra (Journal of Education, Health and Sport, 2021)
Introduction: Osteoarthritis of the knee joint is one of the most common ailments of the lower limb. The popularity of ailments depends on age, the older the patient, the more often and to a bigger extent degenerative changes occur. Thanks to the possibilities of modern medicine, degenerative diseases can be treated in a non-invasive and invasive way. The study addresses the problem of pain and the functional state of the knee joint. Aims of the Study: Assessment of the functional and clinical state of a patient withosteoarthritis of the knee joint. Identification of the most common limitations related to everyday activities of patients qualified for arthroplasty of the knee joint. 3. Influence of pain on the functional status of patients with osteoarthritis of the knee. Materials and Methods: The study was conducted at the Department of Orthopedics, Traumatology and Oncology of the Motor System. It was attended by 49 people qualified for arthroplasty, 23 women and 26 men. Each patient underwent a physical examination consisting of 9 questions and a physical examination in which the function of the affected joints was examined. Results: The greatest correlations were between pain and muscle strength. Increased pain affects the reduction of the muscle strength of the knee joint. The next statistically significant variable was the correlation between the advancement degenerative changes and pain. The degree of advancement of degenerative changes statistically significantly influenced the mobility of the joint. Conclusions: Pain is associated with the reduction of the muscle strength of the knee joint. The advanced degenerative process affects the mobility of the joint. Pain increases with the advancement of degenerative changes.